Efficacy of Topical Difluprednate in Control of Inflammation after Phacoemulsification - Rashid, Md Abdur; Rahman, Farhana; Khanam, Mohosana; Shimu, Farjana Sharmeen; Rahman, KM Mizanur; Hossain, Farzana (Journal of National Institute of Ophthalmology, 2022)
Objective: To study the efficacy of topical Difluprednate 0.05% ophthalmic emulsions in control of post-operative inflammation following phacoemulsification. Methods: This randomized control study included hundred diagnosed cases of age-related cataract who visited at the National institute of Ophthalmology and Hospital in Bangladesh over one year period. The patients were divided into two groups –Difluprednate group and Prednisolone group. The post-operative grades of inflammation following phacoemulsification were assessed by slit-lamp examination. Results: In the present study, majority of the patients were in age group of 55 to 65 years. Male: female ratio in Dfluprednate group was 29:21 and in Prednisolone group was 35:15. Anterior chamber flare and cells was seen in 52% of patients in Prednisolone group and in 56% of patients in the Difluprednate group by day 07, which regressed to mild (1-3) in both the groups by day 28. On day 42, the cells and flair were reduced to 4% in Difluprednate group and 8% at Prednisolon group. When the total scoring of all these parameters were compared, in Prednisolone group 34% of the patients persisted with mild (Grade1-3) inflammation on Day 28 as compared with 26% of the patients in Difluprednate group. Conclusion: Both Difluprednate Ophthalmic Emulsion 0.05% eye drops and Prednisolone Acetate 1% eye drops were equally effective in reducing the inflammation following uncomplicated phacoemulsification. With proven efficacy of Difluprednate, we now have a new standard for potency in a topical corticosteroid, with excellent anti-inflammatory properties and an ideal formulation for our patients. J. Natl. Inst. Ophthalmol. 2022; 5(2):37-41